2018
DOI: 10.1055/a-0605-3264
|View full text |Cite
|
Sign up to set email alerts
|

Number of polyps detected is a useful indicator of quality of clinical colonoscopy

Abstract: Background and study aims  Adenoma detection rate (ADR) is a well-known quality indicator (QI) for colonoscopy. It is, however, difficult to evaluate ADR during practice. The aim of this study was to investigate the number of endoscopically detected polyps as a QI for colonoscopy. Patients and methods  This was a retrospective single-center cohort study of 5,190 consecutive patients who underwent colonoscopy from January 2015 to May 2016. Among these patients, we ultimately enrolled 1,937 patients for initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…26 Among all endoscopically detected adenomas, the final histological diagnosis revealed AA in 2%-18.3% of cases. 27,28 Thus, the AA detection rate (7.1%) in our study was similar to these published results. Interestingly, Karsenti et al reported a strong positive relationship between AA detection rate and age among the participants of a similar age to our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…26 Among all endoscopically detected adenomas, the final histological diagnosis revealed AA in 2%-18.3% of cases. 27,28 Thus, the AA detection rate (7.1%) in our study was similar to these published results. Interestingly, Karsenti et al reported a strong positive relationship between AA detection rate and age among the participants of a similar age to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, adenoma detection rate is the main colonoscopy quality indicator [ 26 ]. Among all endoscopically detected adenomas, the final histological diagnosis revealed AA in 2%- 18.3% of cases [ 27 , 28 ]. Thus, the AA detection rate (7.1%) in our study was similar to these published results.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, a longer follow-up would increase the number of events in this category and a significant association would be found as expected. This factor is considered a main quality indicator for the colonoscopy procedure and was associated with subsequent CRC in other studies (Lieberman et al 2000;Amano et al 2018;Lee et al 2018). If no polyps were found, a risk for CRC remained.…”
Section: Discussionmentioning
confidence: 99%
“…We performed propensity score matching analysis using age and sex because male sex as well as old age are strongly correlated with colorectal neoplasia 9 . After propensity score matching, we analyzed a total of 276 age- and sex-matched patients in both groups ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%